Ethnomedical use of Dodonaea viscosa for postpartum perineal wound care among Dani tribe women in Puncak Jaya, Indonesia - Kurniyasi, Kurniyasi; Makaba, Sarce; Hasmi, Hasmi; Ruru, Yacob; Flassy, Marlina; Irab, Semuel Piter (Jurnal Kesehatan Ibu dan Anak, 2024)
Maternal mortality remains a pressing issue in many developing countries, with postpartum infections being one of the leading causes. In remote regions of Indonesia, such as the highlands of Papua, traditional healing practices are still widely adopted due to limited access to formal health services. Among the Dani tribe in Puncak Jaya District, the use of Dolli or Dolingga (Dodonaea viscosa) leaves for perineal wound care after childbirth is a longstanding cultural tradition. This study aimed to explore the ethnomedical practices, preparation methods, and perceived therapeutic effects of Dolli leaves in managing postpartum perineal wounds among women in the Dani tribe. A qualitative exploratory design was employed. Data were collected through in-depth interviews with 10 postpartum mothers and 2 key informants, including a health official from the Puncak Jaya District Health Office. Thematic content analysis was applied to identify key patterns and cultural meanings associated with the use of Dolli leaves. The use of Dolli leaves is a generational practice, valued for its accessibility and safety. Leaves are wilted over fire to release their oils, then layered (approximately 3 cm thick), and applied externally by having the mother sit or lie on them. Most participants reported improved perineal wound conditions within 1–4 days, characterized by dryness, lack of odor, and absence of infection. Mild abdominal discomfort was noted by some, though no adverse effects were reported. Cultural taboos such as not stepping on the leaves were observed during use. The leaves were also applied for neonatal umbilical cord care. The ethnomedical use of Dolli leaves for postpartum perineal wound healing reflects culturally embedded knowledge with perceived therapeutic benefits. These findings suggest potential for integrating local ethnomedicine into maternal care in resource-limited settings, pending further clinical and pharmacological validation.